2023
DOI: 10.3389/fimmu.2023.1066527
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes of neoadjuvant chemotherapy plus camrelizumab compared with chemotherapy alone and chemoradiotherapy for locally advanced esophageal squamous cell cancer

Abstract: PurposeNeoadjuvant chemoimmunotherapy (nCIT) is becoming a new therapeutic frontier for resectable esophageal squamous cell carcinoma (ESCC); however, crucial details and technical know-how regarding surgical techniques and the perioperative challenges following nCIT remain poorly understood. The study investigated and compared the advantages and disadvantages of esophagectomy following nCIT with neoadjuvant chemotherapy (nCT) and chemoradiotherapy (nCRT).MethodsWe retrospectively analyzed data of patients ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…NCIT did not increase surgical difficulty in our cases, and there were no surgical complications that resulted in death. Zhang et al 38 found that compared to nCRT, nCIT achieved comparable pCR and MPR rates, but with significantly more lymph nodes removed during surgery, shorter operation time, reduced intraoperative blood loss, and fewer ICU admissions post‐surgery.…”
Section: Discussionmentioning
confidence: 99%
“…NCIT did not increase surgical difficulty in our cases, and there were no surgical complications that resulted in death. Zhang et al 38 found that compared to nCRT, nCIT achieved comparable pCR and MPR rates, but with significantly more lymph nodes removed during surgery, shorter operation time, reduced intraoperative blood loss, and fewer ICU admissions post‐surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Research of neoadjuvant chemotherapy combined with immunotherapy for resectable esophageal cancer has made some progress[ 15 ], which shows that neoadjuvant chemotherapy combined with immunotherapy has a high pathological complete response (pCR) rate, which gives a new option for the treatment of locally advanced esophageal cancer. Most clinical studies of neoadjuvant chemotherapy combined with immunotherapy are phase I/II studies, among which the typical one was the National Institute for Health and Care Excellence (NICE) study reported at the European Society for Medical Oncology conference in 2020[ 16 ].…”
Section: Neoadjuvant Chemotherapy Combined With Immunotherapy Before ...mentioning
confidence: 99%
“…Several studies have demonstrated that NICT produced a higher pathological complete response (pCR) rate ranging from 21.7% to 50% with manageable toxicity profile (Zhang et al 2021 ; Yang et al 2022 ; Liu et al 2022a , b . Lv et al 2022 , 2023 ; Yan et al 2022 ; Liu et al 2022a , b ; Zhang et al 2022b ; Chen et al 2023b ; Zhang et al 2023a , b ; Yang et al 2023 ; Yin et al 2022 ; Wang et al 2023 ; Shen et al 2021 ). However, few studies have compared the efficacy and safety of NICT and NCT alone, especially survival outcomes.…”
Section: Introductionmentioning
confidence: 99%